Lung Cancer Surgery Part F: Surgical Treatment Modalities for Pulmonary Metastases - (:unkn) unknown (BENTHAM SCIENCE PUBL, 2013)
Pulmonary metastasectomy has been widely used treatment modality in selected patients with pulmonary metastases due to primary tumour, initiated at some other site. Presence of any metastases in a view may yield an uncontrolled tumoural disease, isolated pulmonary metastases do not consistently represent a systemic or untreatable spread of a primary neoplasm. Making an appropriate surgical resection for isolated pulmonary metastases may help in patients' survival positively. Approach to pulmonary metastases including patient selection, surgical treatment modalities and outcomes of surgery will be discussed in this chapter.
Keywords: Pulmonary metastases; surgery; MEDIAN STERNOTOMY; RESECTION